Polyamide composition with high modulus and low dielectric constant and use thereof

By combining solid and hollow glass reinforcement materials with alloys of polyamide and polyolefins, adjusting the proportion of hollow glass beads, the problem that existing materials are difficult to balance between high modulus and low dielectric constant is solved, and efficient signal transmission and data exchange are achieved.

CN114127182BActive Publication Date: 2025-04-04ARKEMA FRANCE SA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080050562.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-11
Filing Date
2020-06-10
Publication Date
2025-04-04
Estimated Expiration
2040-06-10

AI Technical Summary

Technical Problem

While existing materials pursue high modulus and low dielectric constant, it is difficult to take into account the integrity of signal transmission and the speed of data exchange.

Method used

Compositions with high modulus and low dielectric constants are prepared by adjusting the proportion of hollow glass beads and the formulation of the composition using a mixture of solid and hollow glass reinforcement materials and an alloy consisting of at least one polyamide and at least one polyolefin.

Benefits of technology

The composition has a frequency stability of at least 8 GPa and a dielectric constant of less than or equal to 3.5 under drying conditions at 23°C, ensuring the integrity of signal transmission and the speed of data exchange.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003464579550000291
    Figure BDA0003464579550000291
  • Figure BDA0003464579550000292
    Figure BDA0003464579550000292
  • Figure BDA0003464579550000301
    Figure BDA0003464579550000301
Patent Text Reader

Abstract

The invention relates to the use of a mixture of solid and hollow glass reinforcements, comprising 5% to 50% by weight of hollow glass beads, in particular 5% to 35% by weight of hollow glass beads, relative to the sum of the solid and hollow glass reinforcements, and an alloy consisting of at least one polyamide and at least one polyolefin, for the dry preparation at 23° C. of a composition having a modulus at least equal to 8 GPa, in particular at least equal to 10 GPa, in particular at least equal to 11 GPa, and a dielectric constant Dk less than or equal to 3.5, in particular less than or equal to 3.3, in particular less than or equal to 3.2, measured at a frequency of at least 1 GHz, in particular at a frequency of at least 2 GHz, in particular at a frequency of at least 3 GHz, at 23° C., at 50% RH according to ASTM D-2520-13.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the use of a mixture of solid and hollow glass reinforcements with an alloy (alloy, blend) consisting of at least one polyamide and at least one polyolefin for producing a composition having a high modulus and a low dielectric constant, a process for producing the same and said composition. Prior art

[0002] Original equipment manufacturers (OEMs), especially those for electronics, telecommunications or data exchange applications (e.g., autonomous vehicles or interconnect applications), are increasingly interested in materials with low dielectric constants for protecting or encapsulating such devices.

[0003] Indeed, the advantage of integrating such materials into the casing of, for example, a mobile phone is that the integrity of the signal in antenna applications is guaranteed, thereby ensuring full, high-speed signal transmission.

[0004] Furthermore, in the case of data exchange, the dielectric constant must be as low as possible to ensure the fastest possible data exchange.

[0005] Therefore, the main challenge for such applications is to have the lowest dielectric properties while maintaining a very rigid protective or cladding material. However, in order to obtain a rigid protective or cladding material, it is usually necessary to use glass fibers, which will give the material a higher modulus and therefore higher stiffness.

[0006] However, it is known that the presence of standard glass fibers, for example in a telephone casing, ensures good rigidity of said casing, but also significantly increases the dielectric constant and thus disturbs the signal transmission.

[0007] Therefore, there is a need for a material that exhibits both stiffness and therefore high modulus properties while maintaining a low dielectric constant, thereby ensuring complete and high-speed signal transmission or the fastest possible data exchange.

[0008] The abovementioned problems have therefore been solved by the present invention, which relates to the use of a mixture of solid and hollow glass reinforcements, comprising 5 to 50% by weight, relative to the sum of the solid and hollow glass reinforcements, of hollow glass beads, in particular 5 to 35% by weight, relative to the sum of the solid and hollow glass reinforcements, and an alloy consisting of at least one polyamide and at least one polyolefin,

[0009] The use is for dry preparation at 23° C. of a composition having a modulus of at least 8 GPa, particularly at least 10 GPa, particularly at least 11 GPa, and a dielectric constant Dk of less than or equal to 3.5, particularly less than or equal to 3.3, particularly less than or equal to 3.2, measured at a frequency of at least 1 GHz, particularly at a frequency of at least 2 GHz, particularly at a frequency of at least 3 GHz, at 23° C., at 50% RH according to ASTM D-2520-13.

[0010] In other words, the present invention relates to the use of a mixture of solid and hollow glass reinforcements, comprising 5 to 50% by weight, relative to the sum of the solid and hollow glass reinforcements, of hollow glass beads, in particular 5 to 35% by weight, relative to the sum of the solid and hollow glass reinforcements, and an alloy consisting of at least one polyamide and at least one polyolefin,

[0011] The use is for at least maintaining the modulus and reducing the dielectric constant of a composition comprising the mixture and the alloy relative to a composition comprising the alloy and a glass reinforcement without solid glass reinforcement or comprising the alloy and a glass reinforcement without hollow glass reinforcement, the modulus of the composition in the dry state at 23° C. being at least equal to 8 GPa, particularly at least equal to 10 GPa, particularly at least equal to 11 GPa, and the dielectric constant of the composition being less than or equal to 3.5, particularly less than or equal to 3.3, particularly less than or equal to 3.2, the dielectric constant being measured according to ASTM D-2520-13 at a frequency of at least 1 GHz, particularly at a frequency of at least 2 GHz, particularly at a frequency of at least 3 GHz, at 23° C., at 50% RH.

[0012] In one embodiment, the composition of the present invention is free of polyamide 6 and 66.

[0013] The inventors have therefore surprisingly found that the combination of solid and hollow glass reinforcements with an alloy consisting of at least one polyamide and at least one polyolefin and, moreover, with a specific proportion of hollow glass beads relative to the sum of the solid and hollow glass reinforcements makes it possible to produce compositions having a high modulus of at least 8 GPa, in particular at least 10 GPa, in particular at least 11 GPa and a low dielectric constant Dk of less than or equal to 3.5, in particular less than or equal to 3.3, in particular less than or equal to 3.2, thereby making it possible to have rigid materials that can ensure complete, high-speed signal transmission or have the fastest possible data exchange.

[0014] A distinction is made between different moduli, such as tensile modulus, flexural modulus, etc. If we consider the flexural modulus, it is always lower than the tensile modulus.

[0015] These moduli can be affected by temperature and the moisture level in the sample.

[0016] In one embodiment, the modulus defined above corresponds to both the flexural modulus and the tensile modulus, the flexural modulus being measured according to ISO 178:2010 and the tensile modulus (or modulus of elasticity E) being measured according to ISO 527-1 and 2:2012.

[0017] In another embodiment, the modulus defined above corresponds to the flexural modulus and is measured as above.

[0018] In another embodiment, the modulus defined above corresponds to the tensile modulus and is measured as above.

[0019] The dielectric constant is defined as the ratio of the permittivity (absolute permittivity) ε of the material under consideration to the permittivity of a vacuum. It is denoted k or Dk and is measured according to ASTM D-2520-13. This is the relative permittivity.

[0020] It is measured at 50% relative humidity (RH) at 23°C on samples that have been previously dried, in particular at 80°C for 5 days.

[0021] In one embodiment, the composition has a dry modulus at 23°C of at least 8 GPa, and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0022] In one embodiment, the composition has a dry modulus at 23° C. of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0023] In one embodiment, the composition has a dry modulus at 23° C. of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0024] In one embodiment, the composition has a dry modulus at 23°C of at least 8 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0025] In one embodiment, the composition has a dry modulus at 23° C. of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0026] In one embodiment, the composition has a dry modulus at 23° C. of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0027] In one embodiment, the composition has a dry modulus at 23°C of at least 8 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0028] In one embodiment, the composition has a dry modulus at 23° C. of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0029] In one embodiment, the composition has a dry modulus at 23° C. of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0030] In one embodiment, the composition has a dry modulus at 23°C of at least 8 GPa and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0031] In one embodiment, the composition has a dry modulus at 23°C of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0032] In one embodiment, the composition has a dry modulus at 23°C of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0033] In one embodiment, the composition has a dry modulus at 23°C of at least 8 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0034] In one embodiment, the composition has a dry modulus at 23°C of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0035] In one embodiment, the composition has a dry modulus at 23°C of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0036] In one embodiment, the composition has a dry modulus at 23°C of at least 8 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0037] In one embodiment, the composition has a dry modulus at 23°C of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0038] In one embodiment, the composition has a dry modulus at 23°C of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus and the flexural modulus.

[0039] In one embodiment, the composition has a dry modulus at 23° C. of at least 8 GPa and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the flexural modulus.

[0040] In one embodiment, the composition has a dry modulus at 23° C. of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the flexural modulus.

[0041] In one embodiment, the composition has a dry modulus at 23° C. of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the flexural modulus.

[0042] In one embodiment, the composition has a dry modulus at 23° C. of at least 8 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the flexural modulus.

[0043] In one embodiment, the composition has a dry modulus at 23° C. of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the flexural modulus.

[0044] In one embodiment, the composition has a dry modulus at 23° C. of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the flexural modulus.

[0045] In one embodiment, the composition has a dry modulus at 23° C. of at least 8 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the flexural modulus.

[0046] In one embodiment, the composition has a dry modulus at 23° C. of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the flexural modulus.

[0047] In one embodiment, the composition has a dry modulus at 23° C. of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the flexural modulus.

[0048] In one embodiment, the composition has a dry modulus at 23°C of at least 8 GPa and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the flexural modulus.

[0049] In one embodiment, the composition has a dry modulus at 23°C of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the flexural modulus.

[0050] In one embodiment, the composition has a dry modulus at 23° C. of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the flexural modulus.

[0051] In one embodiment, the composition has a dry modulus at 23°C of at least 8 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the flexural modulus.

[0052] In one embodiment, the composition has a dry modulus at 23° C. of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the flexural modulus.

[0053] In one embodiment, the composition has a dry modulus at 23°C of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the flexural modulus.

[0054] In one embodiment, the composition has a dry modulus at 23°C of at least 8 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the flexural modulus.

[0055] In one embodiment, the composition has a dry modulus at 23°C of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the flexural modulus.

[0056] In one embodiment, the composition has a dry modulus at 23°C of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the flexural modulus.

[0057] In one embodiment, the composition has a dry modulus at 23° C. of at least 8 GPa, and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus.

[0058] In one embodiment, the composition has a dry modulus at 23° C. of at least 10 GPa, and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus.

[0059] In one embodiment, the composition has a dry modulus at 23° C. of at least 11 GPa, and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus.

[0060] In one embodiment, the composition has a dry modulus at 23° C. of at least 8 GPa, and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus.

[0061] In one embodiment, the composition has a dry modulus at 23° C. of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus.

[0062] In one embodiment, the composition has a dry modulus at 23° C. of at least 11 GPa, and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus.

[0063] In one embodiment, the composition has a dry modulus at 23° C. of at least 8 GPa, and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus.

[0064] In one embodiment, the composition has a dry modulus at 23° C. of at least 10 GPa, and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus.

[0065] In one embodiment, the composition has a dry modulus at 23° C. of at least 11 GPa, and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at a frequency of at least 1 GHz, the modulus corresponding to the tensile modulus.

[0066] In one embodiment, the composition has a dry modulus at 23°C of at least 8 GPa and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus.

[0067] In one embodiment, the composition has a dry modulus at 23° C. of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus.

[0068] In one embodiment, the composition has a dry modulus at 23°C of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.5 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus.

[0069] In one embodiment, the composition has a dry modulus at 23°C of at least 8 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus.

[0070] In one embodiment, the composition has a dry modulus at 23°C of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus.

[0071] In one embodiment, the composition has a dry modulus at 23° C. of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.3 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus.

[0072] In one embodiment, the composition has a dry modulus at 23°C of at least 8 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus.

[0073] In one embodiment, the composition has a dry modulus at 23°C of at least 10 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus.

[0074] In one embodiment, the composition has a dry modulus at 23°C of at least 11 GPa and a dielectric constant Dk of less than or equal to 3.2 at 50% RH at frequencies up to 2.4 GHz, the modulus corresponding to the tensile modulus.

[0075] The measurement of dielectric loss (tan δ or tan(δ)) (or power factor (tan δ or tan(δ)) is used to determine the insulating state of the composition.

[0076] Advantageously, the composition has a dielectric loss (tan δ) less than or equal to 0.01, measured according to ASTM D-2520-13 at 23° C., at 50% RH, at a frequency of at least 1 GHz, in particular at a frequency of up to 2.4 GHz, on a dry sample.

[0077] The samples were then pre-dried, in particular at 80°C for 5 days, and tested at 23°C at 50% RH.

[0078] In one embodiment, the composition has a dry modulus and dielectric constant Dk at 23°C as defined above in the various embodiments, and a dielectric loss (tan δ) less than or equal to 0.01, measured on a dry sample at 23°C, at 50% RH, at the same frequency as the dielectric constant in the embodiment.

[0079] About Solid and Hollow Glass Reinforcements

[0080] Solid glass reinforcement

[0081] A solid glass reinforcement is a glass fiber material having a solid (as opposed to hollow) structure and can have any shape as long as it is solid.

[0082] These shapes may be circular or non-circular in cross-section.

[0083] A shape with a circular cross-section is defined as a shape that has a distance at any point on its perimeter equal to the center of the shape, thus representing a perfect or nearly perfect circle.

[0084] Therefore, any glass shape that does not have this perfect or near-perfect circle is defined as a shape with a flat cross-section.

[0085] Non-limiting examples of the flat cross-sectional shape are flat shapes such as an ellipse, an oval or a cocoon shape, a star shape, a sheet shape, a cross shape, a polygon, and a ring shape.

[0086] The solid glass shapes may in particular be short solid glass fibers which, before application of the composition, preferably have a length of between 2 and 13 mm, preferably 3 to 8 mm.

[0087] Solid glass fibers can be:

[0088] A circular cross section with a diameter between 4 μm and 25 μm, preferably between 4 and 15 μm.

[0089] or a non-circular cross section having an L / D ratio (wherein L represents the largest dimension of the cross section of the fiber and D represents the smallest dimension of the cross section of said fiber) between 2 and 8, in particular between 2 and 4. L and D can be measured by scanning electron microscopy (SEM).

[0090] Hollow glass reinforcement

[0091] A hollow glass reinforcement is a glass fiber material having a hollow (as opposed to solid) structure, and like a solid glass reinforcement, it can have any shape as long as it is hollow.

[0092] The hollow glass shapes may in particular be short hollow glass fibers which, before application of the composition, preferably have a length of between 2 and 13 mm, preferably 3 to 8 mm.

[0093] Hollow glass fibers refer to glass fibers in which the hollow core (or hole or window) within the fiber is not necessarily concentric with the outer diameter of the fiber.

[0094] Hollow glass fibers can be:

[0095] - a circular cross section with a diameter between 7.5 and 75 μm, preferably between 9 and 25 μm, more preferably between 10 and 12 μm.

[0096] Obviously, the diameter of the hollow core (the term "hollow core" may also be referred to as a hole or a window) is not equal to the outer diameter of the hollow glass fiber.

[0097] Advantageously, the diameter of the hollow core (or hole or window) is from 10% to 80%, in particular from 60% to 80%, of the outer diameter of the hollow fiber.

[0098] or a non-circular cross section having an L / D ratio (wherein L represents the largest dimension of the cross section of the fiber and D represents the smallest dimension of the cross section of said fiber) between 2 and 8, in particular between 2 and 4. L and D can be measured by scanning electron microscopy (SEM).

[0099] The mixture of solid and hollow glass reinforcements contains 5 to 50 wt % of hollow glass beads, based on the sum of solid and hollow glass reinforcements, in particular 5 to 35 wt % of hollow glass beads, based on the sum of solid and hollow glass reinforcements.

[0100] In one embodiment, the mixture of solid and hollow glass reinforcements comprises 10 to 50 wt. % hollow glass beads, relative to the sum of solid and hollow glass reinforcements, in particular 10 to 35 wt. % hollow glass beads, relative to the sum of solid and hollow glass reinforcements.

[0101] In one embodiment, the mixture of solid and hollow glass reinforcements comprises, in addition to the hollow glass beads, solid glass fibers selected from the group consisting of round cross-section glass fibers, flat cross-section glass fibers, and mixtures thereof.

[0102] In one embodiment, the mixture of solid and hollow glass reinforcements comprises 5 to 50% by weight of hollow glass beads, relative to the sum of solid and hollow glass reinforcements, in particular 5 to 35% by weight of hollow glass beads, relative to the sum of solid and hollow glass reinforcements, the hollow glass beads accounting for the entire proportion of the hollow reinforcements.

[0103] In this last embodiment, the mixture of solid and hollow glass reinforcements comprises, in addition to the hollow glass beads which constitute the bulk of the hollow reinforcements, solid glass fibers selected from the group consisting of round cross-section glass fibers, flat cross-section glass fibers, and mixtures thereof.

[0104] Advantageously, the glass reinforcement mixture consists of 50 to 95% by weight of solid glass fibers and 5 to 50% by weight of hollow glass beads, in particular 65 to 95% by weight of solid glass fibers and 5 to 35% by weight of hollow glass beads.

[0105] Advantageously, the glass reinforcement mixture consists of 50 to 90% by weight of solid glass fibers and 10 to 50% by weight of hollow glass beads, in particular 65 to 90% by weight of solid glass fibers and 10 to 35% by weight of hollow glass beads.

[0106] Advantageously, the solid glass fibers are glass fibers having a non-circular cross-section.

[0107] In one embodiment, the solid glass reinforcement material is a glass fiber having Dk>5 at a frequency of 1 MHz to 5 GHz and in particular Dk>5 and Df<0.005 at a frequency of 1 GHz.

[0108] Advantageously, the solid glass reinforcement material is glass fiber having a non-circular cross-section and an elastic modulus of less than 76 GPa measured according to ASTM C1557-03.

[0109] Alloys consisting of at least one polyamide and at least one polyolefin

[0110] Advantageously, the alloy consists of at least one polyamide and at least one polyolefin, the polyamide / polyolefin weight ratio being between 95 / 5 and 50 / 50.

[0111] Polyolefins:

[0112] The polyolefin of the composition may be a grafted (or functionalized) or non-grafted (or non-functionalized) polyolefin or a mixture thereof.

[0113] The grafted polyolefin may be a polymer of an alpha-olefin with a reactive unit (functional group); such a reactive unit is an acid, anhydride or epoxy functional group. By way of example, the aforementioned non-grafted polyolefins may be mentioned, which are however grafted or copolymerized or trimerized with an unsaturated epoxide such as glycidyl (meth)acrylate, or with a carboxylic acid or a corresponding salt or ester such as (meth)acrylic acid (which may be completely or partially neutralized with a metal such as zinc, etc.) or even with a carboxylic anhydride such as maleic anhydride.

[0114] Advantageously, the grafted polyolefin is chosen from: esters of unsaturated carboxylic acids, such as alkyl acrylates or alkyl methacrylates, preferably the alkyl group having 1 to 24 carbon atoms, examples of alkyl acrylates or alkyl methacrylates being in particular methyl methacrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate;

[0115] Vinyl esters of saturated carboxylic acids, for example vinyl acetate or vinyl propionate.

[0116] Advantageously, said grafted polyolefin as defined above is based on polypropylene.

[0117] The non-grafted polyolefin is typically a homopolymer or copolymer of an alpha-olefin or a diene, such as ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 1-docosene, 1-tetracosene, 1-hexacosene, 1-octacosene and 1-triacontene, preferably propylene or ethylene or a diene such as butadiene, which may be mixed with a compatibilizing and functionalizing agent, such as a maleated Lotader. or maleated polyethylene, isoprene or 1,4-hexadiene.

[0118] In particular, the α-olefin homopolymer is selected from low density polyethylene (LDPE), high density polyethylene (HDPE), linear low density polyethylene (LLDPE), very low density polyethylene (VLDPE) and metallocene polyethylene;

[0119] In particular, the copolymer of α-olefin or diene is selected from ethylene / α-olefin polymers, such as ethylene-propylene, ethylene-butene, ethylene-propylene-diene monomer, ethylene-octene, alone or mixed with polyethylene (PE);

[0120] Advantageously, said non-grafted polyolefin as defined above is based on polypropylene.

[0121] The polyolefin of the composition may also be crosslinked or non-crosslinked, or a mixture of at least one crosslinked and / or at least one non-crosslinked.

[0122] Cross-linked polyolefin

[0123] The polyolefin of the composition according to the present invention may be a non-crosslinked polyolefin and / or a crosslinked polyolefin, the non-crosslinked and / or crosslinked polyolefin being present as a phase dispersed in a matrix formed by polyamide.

[0124] The cross-linked polyolefin is derived from the reaction of two or more products having reactive groups between them.

[0125] More particularly, when the polyolefin is a crosslinked polyolefin, it is obtained from at least one product (A) comprising an unsaturated epoxide and at least one product (B) comprising an unsaturated carboxylic anhydride.

[0126] Product (A) is advantageously a polymer comprising an unsaturated epoxide introduced into said polymer by grafting or by copolymerization.

[0127] The unsaturated epoxides may be chosen in particular from the following epoxides:

[0128] - aliphatic glycidyl esters and ethers, for example allyl glycidyl ether, vinyl glycidyl ether, maleic and itaconic acid glycidyl esters, acrylic and methacrylate glycidyl esters, and

[0129] - Cycloaliphatic glycidyl esters and ethers, for example 2-cyclohexene-1-glycidyl ether, cyclohexene-4,5-diglycidyl carboxylate, cyclohexene-4-glycidyl carboxylate, 5-norbornene-2-methyl-2-glycidyl carboxylate and endo-cis-bicyclo(2,2,1)-5-heptene-2,3-diglycidyl dicarboxylate.

[0130] According to a first form, product (A) is a polyolefin grafted with an unsaturated epoxide. Polyolefin is understood to mean a homopolymer or copolymer comprising one or more olefin units such as ethylene, propylene or butene-1 units or any other α-olefin units. As examples of polyolefins, mention may be made of:

[0131] - polyethylene, including low-density polyethylene (LDPE), high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE) and very low-density polyethylene (VLDPE); polypropylene; ethylene / propylene copolymers; elastomeric polyolefins such as ethylene-propylene (EPR or EPM) or ethylene-propylene-diene monomer (EPDM); or metallocene polyethylene obtained by single-site catalysis;

[0132] - styrene / ethylene-butylene / styrene (SEBS) block copolymers; styrene / butadiene / styrene (SBS) block copolymers; styrene / isoprene / styrene (SIS) block copolymers; or styrene / ethylene-propylene / styrene block copolymers;

[0133] - Copolymers of ethylene and at least one product chosen from the group consisting of salts of unsaturated carboxylic acids, esters of unsaturated carboxylic acids and vinyl esters of saturated carboxylic acids. The polyolefin may in particular be a copolymer of ethylene and an alkyl (meth)acrylate or a copolymer of ethylene and vinyl acetate.

[0134] According to a second form, product (A) is a copolymer of an alpha-olefin and an unsaturated epoxide, and advantageously a copolymer of ethylene and an unsaturated epoxide. Advantageously, the amount of unsaturated epoxide may be up to 15% by weight of the copolymer (A), and the amount of ethylene is at least 50% by weight of the copolymer (A).

[0135] More particularly, copolymers of ethylene, vinyl esters of saturated carboxylic acids and unsaturated epoxides and copolymers of ethylene, alkyl (meth)acrylates and unsaturated epoxides may be cited. Preferably, the alkyl group of the (meth)acrylate contains 2 to 10 carbon atoms. Examples of alkyl acrylates or alkyl methacrylates that can be used include methyl acrylate, methyl methacrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate and 2-ethylhexyl acrylate.

[0136] According to an advantageous embodiment of the invention, product (A) is a copolymer of ethylene, methyl acrylate and glycidyl methacrylate or a copolymer of ethylene, n-butyl acrylate and glycidyl methacrylate. In particular, the copolymers sold by ARKEMA under the name AX8900 products for sale.

[0137] According to another form of the invention, product (A) is a product having two epoxide functions, such as the diglycidyl ether of bisphenol A (DGEBA).

[0138] Product (B) is advantageously a polymer comprising an unsaturated carboxylic anhydride introduced into said polymer by grafting or by copolymerization.

[0139] Examples of unsaturated dicarboxylic anhydrides that can be used as a component of the product (B) include maleic anhydride, itaconic anhydride, citraconic anhydride and tetrahydrophthalic anhydride.

[0140] According to a first form, product (B) is a polyolefin grafted with an unsaturated carboxylic anhydride. As mentioned above, the polyolefin is a homopolymer or copolymer comprising one or more olefin units such as ethylene, propylene or butene-1 units or any other α-olefin units. The polyolefin can be selected in particular from the examples of polyolefins listed above for product (A) when product (A) is a polyolefin grafted with an unsaturated epoxide.

[0141] According to a second form, product (B) is a copolymer of an alpha-olefin and an unsaturated carboxylic acid anhydride, and advantageously a copolymer of ethylene and an unsaturated carboxylic acid anhydride. Advantageously, the amount of unsaturated carboxylic acid anhydride may be up to 15% by weight of the copolymer (B) and the amount of ethylene is at least 50% by weight of the copolymer (B).

[0142] In particular, copolymers of ethylene, vinyl esters of saturated carboxylic acids and unsaturated carboxylic anhydrides and copolymers of ethylene, alkyl (meth)acrylates and unsaturated carboxylic anhydrides may be mentioned. Preferably, the alkyl group of the (meth)acrylate contains 2 to 10 carbon atoms. The alkyl acrylate or alkyl methacrylate may be selected from those listed above for product (A).

[0143] According to an advantageous form of the invention, product (B) is a copolymer of ethylene, alkyl (meth)acrylate and unsaturated carboxylic anhydride. Preferably, product (B) is a copolymer of ethylene, ethyl acrylate and maleic anhydride or a copolymer of ethylene, butyl acrylate and maleic anhydride. In particular, the copolymers sold by ARKEMA under the name 4700 and 3410 products for sale.

[0144] It would not go beyond the scope of the present invention if a portion of the maleic anhydride of the product (B) according to the first and second forms just described were partially hydrolyzed.

[0145] Advantageously, the weight contents of product (A) and product (B), denoted respectively [A] and [B], are such that the ratio [B] / [A] is between 3 and 14 and advantageously between 4 and 9.

[0146] In the composition according to the invention, the crosslinked polyolefin may also be obtained from products (A), (B) as described above and at least one product (C) comprising an unsaturated carboxylic acid or an α-ω-aminocarboxylic acid.

[0147] Product (C) is advantageously a polymer comprising an unsaturated carboxylic acid or an α-ω-aminocarboxylic acid, any of these acids being incorporated into the polymer by copolymerization.

[0148] Examples of unsaturated carboxylic acids which can be used as a component of product (C) include acrylic acid, methacrylic acid, the carboxylic anhydrides mentioned above as a component of product (B), these anhydrides being completely hydrolyzed.

[0149] Examples of α-ω-aminocarboxylic acids suitable for use as a component of product (C) include 6-aminocaproic acid, 11-aminoundecanoic acid and 12-aminododecanoic acid.

[0150] The product (C) may be a copolymer of an alpha-olefin and an unsaturated carboxylic acid, and advantageously a copolymer of ethylene and an unsaturated carboxylic acid. Mention may be made in particular of the completely hydrolyzed copolymers of the product (B).

[0151] According to an advantageous form of the invention, product (C) is a copolymer of ethylene and (meth)acrylic acid or a copolymer of ethylene, an alkyl (meth)acrylate and (meth)acrylic acid. The amount of (meth)acrylic acid may be up to 10% by weight and preferably from 0.5% to 5% by weight of the copolymer (C). The amount of alkyl (meth)acrylate is generally between 5% and 40% by weight of the copolymer (C).

[0152] Advantageously, product (C) is a copolymer of ethylene, butyl acrylate and acrylic acid, such as Escor from ExxonMobil TM 5000.

[0153] Preferably, product (C) is a copolymer of ethylene, butyl acrylate and acrylic acid. In particular, the copolymer sold by BASF under the name 3110 products for sale.

[0154] Of course, the crosslinked polyolefin disperse phase can be prepared by reacting one or more products (A) with one or more products (B) and, if appropriate, with one or several products (C).

[0155] As already described in WO 2011 / 015790, catalysts can be used to accelerate the reaction between the reactive functional groups of products (A) and (B). Examples of catalysts are given in this document, which can be used in a weight proportion of 0.1% to 3%, advantageously 0.5% to 1%, based on the total weight of products (A), (B) and, if appropriate, (C).

[0156] Advantageously, the weight contents of product (A), product (B) and product (C), represented by [A], [B] and [C] respectively, are such that the ratio [B] / ([A]+[C]) is between 1.5 and 8, and the weight contents of products (A) and (B) are such that [C]≤[A].

[0157] Advantageously, the ratio [B] / ([A]+[C]) is between 2 and 7.

[0158] Non-cross-linked polyolefin

[0159] The composition according to the invention may comprise at least one non-crosslinked polyolefin in the form of a phase dispersed in a matrix formed by the semicrystalline polyamide.

[0160] A non-crosslinked polyolefin is understood to mean a homopolymer or copolymer as defined above comprising one or more olefin units, such as ethylene, propylene or butene-1 units or any other α-olefin units.

[0161] Advantageously, the composition comprises at least one crosslinked polyolefin as defined above and at least one non-crosslinked polyolefin as defined above.

[0162] In one embodiment, the alloy consists of at least one polyamide and a mixture of a grafted polyolefin based on polypropylene and a non-grafted polyolefin based on polypropylene.

[0163] Polyamide:

[0164] The at least one polyamide is selected from the group consisting of semi-crystalline polyamides, amorphous polyamides, and mixtures thereof.

[0165] Advantageously, said at least one polyamide is chosen from an amorphous single polyamide, a semi-crystalline polyamide and a mixture of two semi-crystalline polyamides.

[0166] In the sense of the present invention, a semicrystalline copolyamide is a polyamide having a glass transition temperature in DSC according to ISO Standard 11357-2:2013 and a melting temperature (Tm) in DSC according to ISO Standard 11357-3:2013, and a crystallization enthalpy measured in DSC according to ISO Standard 11357-3 of 2013 during a cooling step at a rate of 20 K / min of greater than 30 J / g, preferably greater than 40 J / g.

[0167] In the sense of the present invention, an amorphous polyamide is a polyamide which has only a glass transition temperature in DSC according to ISO Standard 11357-2:2013, but not a melting temperature (Tm), or a polyamide which has a very low degree of crystallinity, whose glass transition temperature in DSC according to ISO Standard 11357-2:2013 and melting point are such that the crystallization enthalpy measured in differential scanning calorimetry DSC according to ISO Standard 11357-3:2013 during a cooling step at a rate of 20 K / min is less than 30 J / g, in particular less than 20 J / g, preferably less than 15 J / g.

[0168] The nomenclature used to define polyamides is described in ISO Standard 1874-1:2011 “Plastiques—Material aux polyamides (PA) pour moulage et extrusion—Partie 1: Designation”, in particular on page 3 (Tables 1 and 2) and is familiar to the person skilled in the art.

[0169] In a first variant, the alloy consists of a single polyamide, which is an amorphous polyamide, and at least one polyolefin.

[0170] Amorphous polyamide:

[0171] The amorphous polyamide may be a polyamide of formula A / XY, wherein:

[0172] A is an aliphatic repeating unit obtained by the polycondensation of:

[0173] At least one C5 to C 18 , preferably C6 to C 12 , more preferably C 10 To C 12 Amino acids, or

[0174] At least one C5 to C 18 , preferably C6 to C12 , more preferably C 10 To C 12 lactam, or

[0175] At least one C4-C 36 , preferably C6-C 18 , preferably C6-C 12 , more preferably C 10 -C 12 The aliphatic diamine Ca and at least one C4-C 36 , preferably C6-C 18 , preferably C6-C 12 , more preferably C8-C 12 Dicarboxylic acid Cb;

[0176] XY is an aliphatic repeating unit obtained by the polycondensation of:

[0177] at least one alicyclic diamine, or at least one linear or branched aliphatic diamine X and

[0178] At least one aromatic dicarboxylic acid or at least one aliphatic dicarboxylic acid Y.

[0179] The amino acid may in particular be chosen from 9-aminononanoic acid, 10-aminodecanoic acid, 10-aminoundecanoic acid, 12-aminododecanoic acid and 11-aminoundecanoic acid and derivatives thereof, in particular N-heptyl-11-aminoundecanoic acid, especially 11-aminoundecanoic acid.

[0180] The lactam may be selected from pyrrolidone, 2-piperidone, caprolactam, enantholactam, caprylolactam, nonanolactam, decanolactam, undecanolactam and lauryl lactam, in particular lauryl lactam.

[0181] The C4-C 36 The aliphatic diamines Ca are linear or branched and are especially selected from butanediamine, 1,5-pentamethyldiamine, 2-methyl-1,5-pentanediamine, 1,6-hexamethylenediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, 2,2,4-trimethylhexamethylenediamine, 1,10-decanediamine, 1,11-undecanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,12-dodecanediamine, 1,13-tridecanediamine, 1,14-tetradecanediamine, 1,16-hexadecanediamine, 1,18-octadecanediamine, 1,20-eicosanediamine, 1,22-docosanediamine and fatty acid dimers.

[0182] The C6-C 18The aliphatic diamine Ca is linear or branched and is especially selected from 1,6-hexamethylenediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, 1,10-decanediamine, 1,11-undecanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,12-dodecanediamine, 1,13-tridecanediamine, 1,14-tetradecanediamine, 1,16-hexadecanediamine, 1,18-octadecanediamine.

[0183] The C6-C 12 The aliphatic diamines Ca are linear or branched and are especially selected from 1,6-hexamethylenediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, 1,10-decanediamine, 1,11-undecanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,12-dodecanediamine.

[0184] The C 10 -C 12 The aliphatic diamine Ca is linear or branched and is chosen especially from 1,10-decanediamine, 1,11-undecanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,12-dodecanediamine.

[0185] The C4-C 36 , preferably C6-C 18 , preferably C6-C 12 , more preferably C8-C 12 Dicarboxylic acid Cb;

[0186] The C4-C36 dicarboxylic acid Cb is aliphatic and linear and is chosen in particular from succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid and sebacic acid, undecanedioic acid, dodecanedioic acid, brassylic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanedioic acid and docosanedioic acid.

[0187] The C6-C 18 The dicarboxylic acids Cb are aliphatic and linear and are chosen in particular from adipic acid, pimelic acid, suberic acid, azelaic acid and sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid.

[0188] The C6-C 12The dicarboxylic acids Cb are aliphatic and linear and are chosen especially from adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid and dodecanedioic acid.

[0189] The C8-C 12 The dicarboxylic acids Cb are aliphatic and linear and are chosen especially from suberic acid, azelaic acid, sebacic acid, undecanedioic acid and dodecanedioic acid.

[0190] In the aliphatic repeating units XY, the diamine X may in particular be an alicyclic diamine selected from bis(3,5-dialkyl-4-aminocyclohexyl)methane, bis(3,5-dialkyl-4-aminocyclohexyl)ethane, bis(3,5-dialkyl-4-aminocyclohexyl)propane, bis(3,5-dialkyl-4-aminocyclohexyl)butane, bis-(3-methyl-4-aminocyclohexyl)-methane (BMACM or MACM), p-bis(aminocyclohexyl)-methane (PACM) and isopropylidenebis(cyclohexylamine) (PACP), isophoronediamine, piperazine, amino-ethylpiperazine.

[0191] It may also include the following carbon skeletons: norbornylmethane, cyclohexylmethane, dicyclohexylpropane, di(methylcyclohexyl), di(methylcyclohexyl)propane. A non-exhaustive list of these cycloaliphatic diamines is given in the publication "Cycloaliphatic Amines" (Encyclopaedia of Chemical Technology, Kirk-Othmer, 4th edition (1992), pages 386-405).

[0192] In the aliphatic repeating units XY, the diamine X may in particular be a linear or branched aliphatic diamine and be chosen from those defined above for the diamines Ca.

[0193] In the aliphatic repeating unit XY, the diacid Y may be an aromatic dicarboxylic acid selected from terephthalic acid (denoted as T), isophthalic acid (denoted as I) and naphthalene dicarboxylic acid.

[0194] In the aliphatic repeating unit XY, the diacid Y may be an aliphatic dicarboxylic acid Y and is selected from those defined above for the diacid Cb.

[0195] Obviously, the unit XY is different from the diamine unit Ca. Diacid Cb.

[0196] Advantageously, A is an aliphatic repeating unit obtained by polycondensation of at least one C5 to C 18 , preferably C6 to C 12 , more preferably C 10 To C 12 Amino acids, or

[0197] At least one C5 to C18 , preferably C6 to C 12 , more preferably C 10 To C 12 Lactam.

[0198] Advantageously, XY is an aliphatic repeating unit obtained by polycondensation of at least one cycloaliphatic diamine and at least one aromatic dicarboxylic acid or at least one aliphatic dicarboxylic acid Y.

[0199] Advantageously, A is an aliphatic repeating unit obtained by polycondensation of at least one C5 to C 18 , preferably C6 to C 12 , more preferably C 10 To C 12 Amino acids, or

[0200] At least one C5 to C 18 , preferably C6 to C 12 , more preferably C 10 To C 12 lactam, and XY is an aliphatic repeating unit obtained by polycondensation of at least one alicyclic diamine and at least one aromatic dicarboxylic acid or at least one aliphatic dicarboxylic acid Y.

[0201] Advantageously, A is an aliphatic repeating unit obtained by polycondensation of at least one C 10 To C 12 Amino acids or at least one C 10 To C 12 lactam, and XY is an aliphatic repeating unit obtained by polycondensation of at least one alicyclic diamine and at least one aromatic dicarboxylic acid or at least one aliphatic dicarboxylic acid Y

[0202] Advantageously, the amorphous polyamide is chosen from 11 / B10, 12 / B10, 11 / BI / BT, 11 / BI, in particular 11 / B10.

[0203] Advantageously, A is an aliphatic repeating unit obtained by polycondensation of at least one C 10 To C 12 Amino acids or at least one C 10 To C 12 lactam, and XY is an aliphatic repeating unit obtained by polycondensation of at least one alicyclic diamine and at least one aromatic dicarboxylic acid.

[0204] Advantageously, the amorphous polyamide is chosen from 11 / BI / BT and 11 / BI.

[0205] Advantageously, A is an aliphatic repeating unit obtained by polycondensation of at least one C 10 To C 12 Amino acids or at least one C 10To C 12 lactam, and XY is an aliphatic repeating unit obtained by polycondensation of at least one alicyclic diamine and at least one aliphatic dicarboxylic acid Y.

[0206] Advantageously, the amorphous polyamide is selected from 11 / B10, 12 / B10, in particular 11 / B10.

[0207] Advantageously, the alloy consists of a single polyamide that is an amorphous polyamide and a mixture of a grafted polyolefin based on polypropylene and a non-grafted polyolefin based on polypropylene.

[0208] In a second variant, the alloy consists of a single semicrystalline polyamide or a mixture of two semicrystalline polyamides and of at least one polyolefin.

[0209] The polyolefin is as defined above.

[0210] Semi-crystalline polyamide:

[0211] The semi-crystalline polyamide may be chosen from aliphatic polyamides, in particular long-chain polyamides, aramid-aliphatic polyamides and semiaromatic polyamides.

[0212] The expression "aliphatic polyamide" means a homopolyamide or a copolyamide. It is understood that it may be a mixture of aliphatic polyamides.

[0213] The expression "long-chain" means that the average number of carbon atoms per nitrogen atom is greater than 8, in particular from 9 to 18.

[0214] In one embodiment, the polyamide mixture is a mixture of aliphatic polyamides, in particular long-chain polyamides, and aromatic-aliphatic polyamides.

[0215] The aliphatic polyamides are obtainable by polycondensation of lactams which may be selected from pyrrolidone, 2-piperidone, caprolactam, enantholactam, capryllactam, nonanolactam, caprolactam, undecanolactam and lauryl lactam, in particular lauryl lactam.

[0216] The aliphatic polyamides are obtainable by polycondensation of amino acids which may be selected from 9-aminononanoic acid, 10-aminodecanoic acid, 10-aminoundecanoic acid, 12-aminododecanoic acid and 11-aminoundecanoic acid and derivatives thereof, in particular N-heptyl-11-aminoundecanoic acid, especially 11-aminoundecanoic acid.

[0217] Aliphatic polyamides are obtainable by polycondensation of units X1Y1, wherein X1 is a diamine and Y is a dicarboxylic acid.

[0218] X1 may be a linear or branched C5-C18 aliphatic diamine and may in particular be selected from 1,5-pentamethyldiamine, 2-methyl-1,5-pentanediamine, 1,6-hexamethylenediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 2-methyl-1,8-octane-diamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, 1,10-decanediamine, 1,11-undecanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,12-dodecanediamine, 1,13-tridecanediamine, 1,14-tetradecanediamine, 1,16-hexadecanediamine and 1,18-octadecanediamine.

[0219] Advantageously, the diamine X1 used is C6-C12, in particular chosen from butanediamine, pentanediamine, 2-methyl-1,5-pentanediamine, 1,6-hexamethylenediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, 1,10-decanediamine, 1,11-undecanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,12-dodecanediamine.

[0220] Advantageously, the diamine X1 used is C10 to C12, in particular chosen from 1,10-decanediamine, 1,11-undecanediamine, 2-butyl-2-ethyl-1,5-pentanediamine and 1,12-dodecanediamine,

[0221] Y1 may be a C6-C18 aliphatic dicarboxylic acid, particularly C6-C12, especially C10-C12.

[0222] The C6 to C18 aliphatic dicarboxylic acid Y1 may be selected from adipic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid.

[0223] The C6 to C12 aliphatic dicarboxylic acid Y1 may be selected from adipic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid.

[0224] The C10 to C12 aliphatic dicarboxylic acid Y1 may be selected from sebacic acid, undecanedioic acid, dodecanedioic acid.

[0225] Advantageously, the aliphatic polyamide is chosen from PA6, PA66, PA610, PA612, PA1010, PA1012, PA1212, PA11 and PA 12, in particular PA1010, PA1012, PA1212, PA11 and PA 12.

[0226] The expression "aromatic-aliphatic polyamide" is intended to mean a polyamide obtained by polycondensation of units X2Y1, X2 representing an aromatic diamine and Y1 representing an aliphatic dicarboxylic acid, as defined above.

[0227] The aromatic diamine X2 may be selected from meta-xylylenediamine (MXD) and para-xylylenediamine (PXD).

[0228] Advantageously, the aromatic-aliphatic polyamide is selected from MXD6, MXD10, MXD12.

[0229] Advantageously, the aromatic-aliphatic polyamide is selected from MXD10, MXD12.

[0230] Advantageously, the mixture of two semicrystalline polyamides is a mixture of an aliphatic polyamide and an araliphatic polyamide.

[0231] Advantageously, the mixture of two semicrystalline polyamides is a mixture of an aliphatic polyamide chosen from PA6, PA66, PA610, PA612, PA1010, PA1012, PA1212, PA11 and PA 12, in particular PA1010, PA1012, PA1212, PA11 and PA 12, and an aromatic aliphatic polyamide chosen from MXD6, MXD10 and MXD12.

[0232] Advantageously, the mixture of two semicrystalline polyamides is a mixture of an aliphatic polyamide chosen from PA1010, PA1012, PA1212, PA11 and PA 12 and an aromatic aliphatic polyamide chosen from MXD10, MXD12.

[0233] The expression "semiaromatic polyamide" means in particular a semiaromatic polyamide of the formula as described in EP1505099, in particular a semiaromatic polyamide of formula B / ZT, wherein B is chosen from units obtained by polycondensation of amino acids as defined above, units obtained by polycondensation of lactams as defined above and units corresponding to the formula X2Y2, wherein X2 and Y2 are as defined above;

[0234] ZT represents a unit obtained by the polycondensation of a Cx diamine and terephthalic acid, wherein x represents the number of carbon atoms of the Cx diamine, x being between 4 and 36, advantageously between 6 and 18, advantageously between 6 and 12, advantageously between 10 and 12, in particular a polyamide of formula A / 6T, A / 9T, A / 10T or A / 11T, A being as defined above, in particular the polyamides PA 6 / 6T, PA 66 / 6T, PA 61 / 6T, PA 11 / 9T, PA 11 / 10T, PA 11 / 12T, PA 12 / 9T, PA 12 / 10T, PA 12 / 12T, PA MPMDT / 6T, PA MXDT / 6T, PA 11 / 6T / 10T, PA MXDT / 10T, PA MPMDT / 10T, PA BACT / 10T, PA BACT / 6T, PABACT / 10T / 6T, PA 11 / BACT / 10T, PA 11 / MPMDT / 10T, and PA 11 / MXDT / 10T, as well as block copolymers, in particular polyamide / polyether (PEBA).

[0235] T corresponds to terephthalic acid, MXD corresponds to meta-xylene diamine, MPMD corresponds to methylpentamethylene diamine and BAC corresponds to bis(aminomethyl)cyclohexane (1,3BAC and / or 1,4BAC).

[0236] Advantageously, the semiaromatic polyamide is chosen from PA11 / 9T, PA11 / 10T, PA 11 / 12T, PA12 / 9T, PA12 / 10T, PA12 / 12T.

[0237] Advantageously, the at least one polyamide is chosen from: single amorphous polyamides, aromatic-aliphatic polyamides, mixtures of aliphatic polyamides, in particular long-chain polyamides, with aromatic-aliphatic polyamides, and mixtures of aliphatic polyamides, in particular long-chain polyamides, with semiaromatic polyamides.

[0238] Advantageously, the alloy consists of a mixture of two semicrystalline polyamides and a mixture of a grafted polyolefin based on polypropylene and a non-grafted polyolefin based on polypropylene.

[0239] In one embodiment, the invention relates to the use as defined above, wherein the composition comprises an additive.

[0240] additive

[0241] The additives may be present up to 2% by weight, based on the total weight of the composition, in particular they are present from 1% to 2% by weight relative to the total weight of the composition.

[0242] The additives may be selected from catalysts, antioxidants, heat stabilizers, UV stabilizers, light stabilizers, lubricants, flame retardants, nucleating agents, chain extenders and colorants.

[0243] The term "catalyst" refers to a polycondensation catalyst, such as an inorganic acid or an organic acid.

[0244] Advantageously, the proportion by weight of the catalyst is from about 50 ppm to about 5000 ppm, in particular from about 100 to about 3000 ppm, relative to the total weight of the composition.

[0245] Advantageously, the catalyst is selected from phosphoric acid (H3PO4), phosphorous acid (H3PO3), hypophosphorous acid (H3PO2) or mixtures thereof.

[0246] The antioxidant may in particular be 0.05% to 5% by weight, preferably 0.05% to 1% by weight, preferably 0.1% to 1% of an antioxidant based on a copper complex.

[0247] The expression copper complex denotes in particular a complex between a monovalent or divalent copper salt with an organic or inorganic acid and an organic ligand.

[0248] Advantageously, the copper salt is chosen from copper (Cu(II)) salts of hydrogen halides, cuprous (Cu(I)) salts of hydrogen halides and salts of aliphatic carboxylic acids.

[0249] In particular, the copper salt is selected from CuCl, CuBr, CuI, CuCN, CuCl2, Cu(OAc)2, cuprous stearate.

[0250] Copper complexes are described inter alia in US Pat. No. 3,505,285.

[0251] The copper-based complex may further comprise a ligand selected from the group consisting of phosphines, in particular triphenylphosphine, mercaptobenzimidazole, EDTA, acetylacetonate, glycine, ethylenediamine, oxalate, diethylenediamine, triethylenetetramine, pyridine, tetrabromobiphenyl-A, derivatives of tetraphenyl-A, such as epoxy derivatives, and derivatives of chlorodimethylbenz(a,e)cyclooctene and mixtures thereof, diphosphines and bipyridines or mixtures thereof, in particular triphenylphosphine and / or mercaptobenzimidazole.

[0252] Phosphine represents an alkylphosphine, such as tributylphosphine, or an arylphosphine, such as triphenylphosphine (TPP).

[0253] Advantageously, the ligand is triphenylphosphine.

[0254] Examples of complexes and how to prepare them are described in patent CA 02347258.

[0255] Advantageously, the amount of copper in the composition of the invention ranges from 10 ppm to 1000 ppm by weight, in particular from 20 ppm to 70 ppm, in particular from 50 ppm to 150 ppm, relative to the total weight of the composition.

[0256] Advantageously, the copper-based complex further comprises a halogenated organic compound.

[0257] The halogenated organic compound may be any halogenated organic compound.

[0258] Advantageously, the halogenated organic compound is a bromine-based compound and / or an aromatic compound.

[0259] Advantageously, the aromatic compound is chosen in particular from decabromobiphenyl, decabromodiphenyl ether, bromo- or chlorostyrene oligomers, polydibromostyrene,

[0260] Advantageously, the halogenated organic compound is a bromine-based compound.

[0261] The halogenated organic compound is added to the composition in a proportion of 50 to 30,000 ppm, particularly 100 to 10,000, particularly 500 to 1500 ppm by weight of halogen relative to the total weight of the composition.

[0262] Advantageously, the copper:halogen molar ratio is from 1:1 to 1:3000, in particular from 1:2 to 1:100.

[0263] In particular, the ratio is 1:1.5 to 1:15.

[0264] Advantageously, the antioxidant is based on a copper complex.

[0265] The heat stabilizer may be an organic stabilizer or more generally a combination of organic stabilizers, for example a primary antioxidant of the phenolic type (for example Ciba's irganox 245 or 1098 or 1010 types), or a secondary antioxidant of the phosphite type.

[0266] The UV stabilizer may be a HALS, which means hindered amine light stabilizer, or an anti-UV agent (eg Tinuvin 312 from Ciba).

[0267] Light stabilizers can be hindered amines (such as Tinuvin 770 from Ciba), phenols, or phosphorus-based stabilizers.

[0268] The lubricant may be a fatty acid type lubricant, such as stearic acid.

[0269] The flame retardant may be a halogen-free flame retardant as described in US 2008 / 0274355, and in particular a phosphorus-based flame retardant, for example a metal salt selected from the group consisting of a metal salt of phosphinic acid, in particular a dialkylphosphinate, in particular an aluminum diethylphosphinate or an aluminum diethylphosphinate, a metal salt of a diphosphinic acid, a mixture of an aluminum phosphinate flame retardant and a nitrogen synergist or a mixture of an aluminum phosphinate flame retardant and a phosphorus synergist, a polymer containing at least one metal phosphinate, in particular based on ammonium, such as ammonium polyphosphate, ammonium sulfamate or ammonium pentaborate, or based on melamine, such as melamine, melamine salts, melamine pyrophosphate and melamine cyanurate, or based on cyanuric acid, or a polymer containing at least one metal diphosphinate or red phosphorus, antimony oxide, zinc oxide, iron oxide, magnesium oxide or a metal borate, such as zinc borate, or a phosphazene (phosphazine), a phosphamide or a phosphorus oxynitride or a mixture thereof. It may also be a halogenated flame retardant, for example brominated or polybrominated polystyrene, brominated polycarbonate or brominated phenol.

[0270] The nucleating agent may be silica, alumina, clay or talc, especially talc.

[0271] Examples of suitable chain limiters are monoamines, monocarboxylic acids, diamines, triamines, dicarboxylic acids, tricarboxylic acids, tetraamines, tetracarboxylic acids and oligoamines or oligocarboxylic acids having in each case 5 to 8 amino or carboxyl groups, respectively, and in particular dicarboxylic acids, tricarboxylic acids or mixtures of dicarboxylic acids and tricarboxylic acids. For example, dodecanedicarboxylic acid in the form of a dicarboxylic acid and trimellitic acid as a tricarboxylic acid can be used.

[0272] In another embodiment, the invention relates to the use as defined above, wherein the composition comprises at least one prepolymer, in particular monofunctional NH2, in particular based on PA11.

[0273] Advantageously, the composition comprises a single prepolymer.

[0274] Prepolymer

[0275] The prepolymer may be present up to 11 wt %, based on the total weight of the composition, specifically 0.1 wt % to 11 wt %, based on the total weight of the composition.

[0276] The prepolymer is distinct from the nucleating agent used as an additive.

[0277] The term "prepolymer" refers to an oligomer of polyamide whose number average molecular weight must be lower than that of the polyamide used in the composition, in particular the prepolymer has a number average molecular weight of 1000-15000 g / mol, in particular 1000-10000 g / mol.

[0278] The prepolymer may be selected from aliphatic, linear or branched polyamide oligomers, cycloaliphatic polyamide oligomers, semiaromatic polyamide oligomers, aromatic polyamide oligomers, aliphatic, linear or branched, cycloaliphatic, semiaromatic and aromatic polyamides, which have the same definition as above.

[0279] Thus, a prepolymer or oligomer results from the condensation of:

[0280] - at least one lactam, or

[0281] - at least one amino acid, or

[0282] - at least one diamine and at least one dicarboxylic acid, or a mixture thereof.

[0283] Thus, the prepolymer or oligomer cannot correspond to the condensation of a diamine with a lactam or an amino acid.

[0284] The prepolymer may also be a copolyamide oligomer or a mixture of polyamide and copolyamide oligomers.

[0285] For example, the prepolymer is monofunctional NH2, monofunctional CO2H or difunctional CO2H or NH2.

[0286] Thus, the prepolymer may be a monofunctional or difunctional acid or amine, i.e. it has a single terminal amine or acid function when it is monofunctional (in which case the other end is non-functional, particularly CH3), or two terminal amine functions or two terminal acid functions when it is difunctional.

[0287] Advantageously, the prepolymer is monofunctional, preferably NH2 or CO2H.

[0288] It may also be non-functional at both ends, especially di-CH3.

[0289] In one embodiment, the invention relates to the use as defined above, wherein the composition comprises:

[0290] 30% to 70% by weight, in particular 35% to 60% by weight and more particularly 40% to 50% by weight of an alloy as defined above consisting of at least one polyamide and at least one polyolefin, the polyamide / polyolefin ratio being between 95 / 5 and 50 / 50;

[0291] 30% to 70% by weight, in particular 40% to 65% by weight and more particularly 50% to 60% by weight of a mixture of solid and hollow glass reinforcements as defined above; and

[0292] 0% to 11% by weight of at least one prepolymer, in particular 0.1% to 11%;

[0293] 0% to 5% filler and

[0294] 0 to 2% by weight, preferably 1 to 2% by weight, of additives,

[0295] The sum of the proportions of each component of the composition equals 100%.

[0296] In another embodiment, the invention relates to the use as defined above, wherein the composition consists of:

[0297] 30% to 70% by weight, in particular 35% to 60% by weight and more particularly 40% to 50% by weight of an alloy as defined above consisting of at least one polyamide and at least one polyolefin, the polyamide / polyolefin ratio being between 95 / 5 and 50 / 50;

[0298] 30% to 70% by weight, in particular 40% to 65% by weight and more particularly 50% to 60% by weight of a mixture of solid and hollow glass reinforcements as defined above; and

[0299] 0% to 11% by weight of at least one prepolymer, in particular 0.1% to 11%;

[0300] 0% to 5% filler and

[0301] 0 to 2% by weight, preferably 1 to 2% by weight, of additives,

[0302] The sum of the proportions of each component of the composition equals 100%.

[0303] In one embodiment, the invention relates to the use as defined above, wherein the composition comprises:

[0304] 30% to 50% by weight, in particular 35% to 50% by weight and more particularly 40% to 50% by weight of an alloy as defined above consisting of at least one polyamide and at least one polyolefin, the polyamide / polyolefin ratio being between 95 / 5 and 50 / 50;

[0305] 50% to 70% by weight, in particular 50% to 65% by weight and more particularly 50% to 60% by weight of a mixture of solid and hollow glass reinforcements as defined above; and

[0306] 0% to 11% by weight of at least one prepolymer, in particular 0.1% to 11%;

[0307] 0% to 5% filler and

[0308] 0 to 2% by weight, preferably 1 to 2% by weight, of additives,

[0309] The sum of the proportions of each component of the composition equals 100%.

[0310] In yet another embodiment, the invention relates to the use as defined above, wherein the composition consists of:

[0311] 30% to 50% by weight, in particular 35% to 50% by weight and more particularly 40% to 50% by weight of an alloy as defined above consisting of at least one polyamide and at least one polyolefin, the polyamide / polyolefin ratio being between 95 / 5 and 50 / 50;

[0312] 50% to 70% by weight, in particular 50% to 65% by weight and more particularly 50% to 60% by weight of a mixture of solid and hollow glass reinforcements as defined above; and

[0313] 0% to 11% by weight of at least one prepolymer, in particular 0.1% to 11%;

[0314] 0% to 5% filler and

[0315] 0 to 2% by weight, preferably 1 to 2% by weight, of additives,

[0316] The sum of the proportions of each component of the composition equals 100%.

[0317] According to another aspect, the present invention relates to a composition, particularly useful for injection molding, comprising:

[0318] 30% to 70% by weight, in particular 35% to 60% by weight and more particularly 40% to 50% by weight of an alloy as defined above consisting of at least one polyamide and at least one polyolefin, the polyamide / polyolefin ratio being between 95 / 5 and 50 / 50;

[0319] 30% to 70% by weight, in particular 40% to 65% by weight and more particularly 50% to 60% by weight of a mixture of solid and hollow glass reinforcements as defined above; and

[0320] 0% to 11% by weight of at least one prepolymer, in particular 0.1% to 11%;

[0321] 0% to 5% filler and

[0322] 0 to 2% by weight, preferably 1 to 2% by weight, of additives,

[0323] The sum of the proportions of each component of the composition equals 100%.

[0324] Advantageously, the composition, particularly useful for injection molding, consists of:

[0325] 30% to 70% by weight, in particular 35% to 60% by weight and more particularly 40% to 50% by weight of an alloy as defined above consisting of at least one polyamide and at least one polyolefin, the polyamide / polyolefin ratio being between 95 / 5 and 50 / 50;

[0326] 30% to 70% by weight, in particular 40% to 65% by weight and more particularly 50% to 60% by weight of a mixture of solid and hollow glass reinforcements as defined above; and

[0327] 0% to 11% by weight of at least one prepolymer, in particular 0.1% to 11%;

[0328] 0% to 5% filler and

[0329] 0 to 2 wt%, 1 to 2 wt% of additives,

[0330] The sum of the proportions of each component of the composition equals 100%.

[0331] In one embodiment, the composition, particularly useful for injection molding, comprises:

[0332] 30% to 50% by weight, in particular 35% to 50% by weight and more particularly 40% to 50% by weight of an alloy as defined above consisting of at least one polyamide and at least one polyolefin, the polyamide / polyolefin ratio being between 95 / 5 and 50 / 50;

[0333] 50% to 70% by weight, in particular 50% to 65% by weight and more particularly 50% to 60% by weight of a mixture of solid and hollow glass reinforcements as defined above; and

[0334] 0% to 11% by weight of at least one prepolymer, in particular 0.1% to 11%;

[0335] 0% to 5% filler and

[0336] 0 to 2% by weight, preferably 1 to 2% by weight, of additives,

[0337] The sum of the proportions of each component of the composition equals 100%.

[0338] In another embodiment, the composition, particularly useful for injection molding, consists of:

[0339] 30% to 50% by weight, in particular 35% to 50% by weight and more particularly 40% to 50% by weight of an alloy as defined above consisting of at least one polyamide and at least one polyolefin, the polyamide / polyolefin ratio being between 95 / 5 and 50 / 50;

[0340] 50% to 70% by weight, in particular 50% to 65% by weight and more particularly 50% to 60% by weight of a mixture of solid and hollow glass reinforcements as defined above; and

[0341] 0% to 11% by weight of at least one prepolymer, in particular 0.1% to 11%;

[0342] 0% to 5% filler and

[0343] 0 to 2% by weight, preferably 1 to 2% by weight, of additives,

[0344] The sum of the proportions of each component of the composition equals 100%.

[0345] In one embodiment, the composition is free of polyamide 6 and 66.

[0346] All features defined above for the above defined uses are valid for the composition itself.

[0347] About filler

[0348] The composition may also contain fillers. Contemplated fillers include conventional mineral fillers such as kaolin, magnesium oxide, slag, carbon black, expanded or unexpanded graphite, wollastonite, pigments such as titanium oxide and zinc sulfide, and antistatic fillers.

[0349] Advantageously, the composition, particularly useful for injection molding, consists of:

[0350] 30% to 70% by weight, in particular 35% to 60% by weight and more particularly 40% to 50% by weight of an alloy as defined above consisting of at least one polyamide and at least one polyolefin, the polyamide / polyolefin ratio being between 95 / 5 and 50 / 50;

[0351] 30% to 70% by weight, in particular 40% to 65% by weight and more particularly 50% to 60% by weight of a mixture of solid and hollow glass reinforcements as defined above; and

[0352] 0 to 11% by weight of at least one prepolymer, in particular 0.1 to 11% by weight;

[0353] 0 to 5 wt% filler, and

[0354] 0 to 2% by weight, preferably 1 to 2% by weight, of additives,

[0355] The sum of the proportions of each component of the composition equals 100%.

[0356] According to another aspect, the invention relates to the use of a composition as defined above for the manufacture of an article, in particular for electronics, for telecommunication applications or for data exchange, such as for autonomous vehicles or for applications connected to one another.

[0357] Advantageously, the article is manufactured by injection moulding.

[0358] In other words, the invention relates to a method for preparing an article, in particular for electronic products, for telecommunication applications or for data exchange, for example for autonomous vehicles or for interconnect applications, comprising a step carried out in particular by injection moulding a composition as defined above.

[0359] According to another aspect, the invention relates to an article obtained by injection moulding with a composition as defined above. Example

[0360] The present invention will now be illustrated in more detail by the following examples, without being limited thereto in any way.

[0361] The various polyamides and copolyamides of the present invention are prepared according to conventional techniques for the synthesis of polyamides and copolyamides.

[0362] Synthesis of CoPa 11 / 10T, representing various copolyamides:

[0363] Aminoundecanoic acid, decanediamine and terephthalic acid monomer are loaded together in a reactor according to the desired mass ratio. First, the medium is inertized to remove oxygen that can produce yellowing or secondary reactions. Water can also be loaded to improve heat exchange. Two temperature increases and pressure platforms are carried out. Temperature (T°) and pressure conditions are selected to allow the medium to melt. After reaching the maintenance conditions, degassing is carried out to allow polycondensation. The medium gradually becomes sticky and the reaction water formed is entrained by purging with nitrogen or applying vacuum. When the stop condition related to the desired viscosity is reached, stirring is stopped and extrusion and granulation can be started.

[0364] The compositions (weight %) in Table 1 were prepared according to the following general protocol:

[0365] Compounding of the granules used to prepare the formulation:

[0366] Twin-screw extruders, such as Coperion ZSK 26MC, with at least 1 transverse raw material inlet

[0367] Machine temperature: 270C

[0368] Screw speed: 250rpm

[0369] Extruder output: 16kg / h

[0370] Conversion:

[0371] Wafers of 100x100x2 mm3 were manufactured by injection molding for measuring dielectric properties. The following parameters were used:

[0372] -ENGEL VICTORY 500,160T hydraulic press

[0373] -Injection temperature (feed / nozzle): 265C / 280C

[0374] -Mold temperature: 100C

[0375] -Hold time: 10s

[0376] -Material holding pressure: 700bar

[0377] -Cooling time: 35s

[0378] Dumbbell-shaped specimens according to ISO 527-2 1A were prepared by injection molding for measuring tensile mechanical properties. The following parameters were used:

[0379] -ENGEL VICTORY 500,160T hydraulic press

[0380] -Injection temperature (feed / nozzle): 285C / 295C

[0381] -Mold temperature: 100C

[0382] -Hold time: 10s

[0383] -Material holding pressure: 700bar

[0384] -Cooling time: 15s

[0385] The results obtained with the compositions of the present invention are shown in Tables 1 and 2 below:

[0386] Table 1

[0387]

[0388]

[0389]

[0390] The comparative compositions are shown in Table 3 below:

[0391] Table 3

[0392]

[0393] I1 to I9: Inventions 1 to 9

[0394] C1 to C13: Comparative compositions C1 to C13

[0395] N / A: Not tested

[0396] PA11: Rilsan (Arkema)

[0397] PA11 / 10T (28 / 72 by weight)

[0398] PA11 / B10 (10 / 90 by weight)

[0399] Polypropylene PPH 5060: Non-grafted polypropylene homopolymer from Total

[0400] Orevac CA 100: Maleic anhydride grafted polypropylene (Arkema)

[0401] PA oligomer: PA11 mono NH2

[0402] The antioxidant refers to a phenolic type antioxidant.

[0403] The secondary antioxidant corresponds to a phosphite-type antioxidant.

[0404] NE Glass Fiber: NE solid glass fiber with flat cross section from Nitto Boseki

[0405] E glass fiber: E solid glass fiber with a circular cross section from Nitto Boseki or Nippon Electric Glass

[0406] HM Glass Fiber: Solid fiber with a circular cross section from AGY (high modulus glass fiber)

[0407] Glass beads: Hollowlite glass beads

[0408] Dk, tanδ are measured according to ASTM D-2520-13

[0409] The tensile modulus (or elastic modulus E) is measured according to ISO 527-1 and 2:2012.

Claims

1. Use of a mixture of solid and hollow glass reinforcements, comprising 5 to 50% by weight of hollow glass beads, relative to the sum of the solid and hollow glass reinforcements, with an alloy consisting of at least one polyamide and at least one polyolefin, wherein the alloy consists of a mixture of two semicrystalline polyamides and at least one polyolefin, the polyamide mixture being a mixture of an aliphatic polyamide with an aromatic-aliphatic polyamide, Excluding polyamide 6 and 66, The use is for dry preparation at 23° C. of a composition having a modulus at least equal to 8 GPa and a dielectric constant Dk less than or equal to 3.5 measured at a frequency of at least 1 GHz, at 23° C., at 50% RH according to ASTM D-2520-13.

2. The method according to claim 1, wherein the mixture of solid and hollow glass reinforcements comprises 5% to 35% by weight of hollow glass beads, relative to the sum of the solid and hollow glass reinforcements.

3. Use according to claim 1, wherein said composition has a modulus at least equal to 10 GPa.

4. Use according to claim 3, wherein said composition has a modulus at least equal to 11 GPa.

5. The use according to claim 1, wherein the composition has a dielectric constant Dk less than or equal to 3.

3.

6. The use according to claim 5, wherein the composition has a dielectric constant Dk less than or equal to 3.

2.

7. The use according to claim 1, wherein the dielectric constant Dk is measured at a frequency of at least 2 GHz.

8. Use according to claim 7, wherein the dielectric constant Dk is measured at a frequency of at least 3 GHz.

9. The use according to claim 1, wherein the dielectric loss (tan δ) of the composition is less than or equal to 0.01, measured according to ASTM D-2520-13 at 23°C, at 50% RH, at a frequency of at least 1 GHz, on a dry sample.

10. Use according to claim 9, wherein the dielectric loss (tan δ) of the composition is measured at a frequency of up to 2.4 GHz.

11. The use according to any one of claims 1 to 10, wherein the mixture of solid and hollow glass reinforcements, in addition to hollow glass beads, further comprises solid glass fibers selected from the group consisting of round cross-section glass fibers, flat cross-section glass fibers and mixtures thereof.

12. The use according to claim 11, wherein the mixture of glass reinforcements consists of 50% to 95% by weight of solid glass fibers and 5% to 50% by weight of hollow glass beads.

13. The use according to claim 12, wherein the mixture of glass reinforcements consists of 65% to 95% by weight of solid glass fibers and 5% to 35% by weight of hollow glass beads.

14. Use according to any one of claims 1 to 10, wherein the alloy consists of a mixture of two semicrystalline polyamides and at least one polyolefin, the polyamide / polyolefin weight ratio being between 95 / 5 and 50 / 50.

15. Use according to any one of claims 1 to 10, wherein the at least one polyolefin is selected from grafted polyolefins and non-grafted polyolefins and mixtures thereof.

16. Use according to claim 15, wherein the at least one polyolefin is a mixture of grafted polyolefin and non-grafted polyolefin.

17. The use according to claim 15, wherein the reactive units of the grafted polyolefin are selected from: esters of unsaturated carboxylic acids; vinyl esters of saturated carboxylic acids.

18. The use according to claim 17, wherein the ester of the unsaturated carboxylic acid is selected from alkyl acrylates or alkyl methacrylates.

19. Use according to claim 18, wherein the alkyl group has 1 to 24 carbon atoms.

20. The use according to claim 18, wherein the alkyl acrylate or alkyl methacrylate is selected from methyl methacrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate or 2-ethylhexyl acrylate.

21. The use according to claim 17, wherein the vinyl ester of a saturated carboxylic acid is selected from vinyl acetate or vinyl propionate.

22. The use according to claim 15, wherein the grafted polyolefin is propylene based.

23. The use according to claim 15, wherein the non-grafted polyolefin is selected from ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 1-docosene, 1-tetracosene, 1-hexacosene, 1-octacosene, 1-triacontene, or a diene.

24. Use according to claim 23, wherein the non-grafted polyolefin is selected from propylene or ethylene.

25. Use according to claim 23, wherein the diene is selected from butadiene, isoprene or 1,4-hexadiene.

26. The use according to claim 15, wherein the non-grafted polyolefin is propylene based.

27. Use according to claim 14, wherein the alloy consists of a mixture of two semi-crystalline polyamides and a mixture of a grafted polyolefin based on polypropylene and a non-grafted polyolefin based on polypropylene.

28. The use according to claim 1, wherein the aliphatic polyamide is a long-chain polyamide.

29. The use according to claim 1, wherein the aliphatic polyamide is selected from PA610, PA612, PA1010, PA1012, PA1212, PA11 and PA 12.

30. The use according to claim 29, wherein the aliphatic polyamide is selected from PA1010, PA1012, PA1212, PA11 or PA 12.

31. The use according to claim 1, wherein the aromatic-aliphatic polyamide is selected from MXD6, MXD10, MXD12.

32. Use according to one of claims 1 to 10, wherein the composition comprises an additive.

33. Use according to one of claims 1 to 10, wherein the composition comprises at least one prepolymer.

34. The use according to claim 33, wherein the prepolymer is monofunctional NH2.

35. Use according to claim 33, wherein the prepolymer is based on PA11.

36. A composition comprising: 30% to 70% by weight of an alloy consisting of a mixture of two semicrystalline polyamides and at least one polyolefin as defined in one of claims 1 to 31, the polyamide / polyolefin ratio being from 95 / 5 to 50 / 50; 30% to 70% by weight of a mixture of solid and hollow glass reinforcements as defined in one of claims 1 to 31; Excluding polyamide 6 and 66, and 0 to 11 wt % of at least one prepolymer; 0 to 5 wt% filler, and 0 to 2% by weight of additives, The sum of the proportions of each component of the composition equals 100%.

37. The composition of claim 36, wherein the composition is useful for injection molding.

38. The composition of claim 36, wherein the composition comprises 35 to 60 weight percent of the alloy.

39. The composition of claim 38, wherein the composition comprises 40 to 50 weight percent of the alloy.

40. The composition of claim 36, wherein the composition comprises 40% to 65% by weight of the mixture of solid and hollow glass reinforcements.

41. The composition of claim 40, wherein the composition comprises 50% to 60% by weight of the mixture of solid and hollow glass reinforcements.

42. The composition of claim 36, wherein the composition comprises from 0.1% to 11% of at least one prepolymer.

43. The composition of claim 36, wherein the composition comprises 1 wt% to 2 wt% of the additive.

44. Use of a composition as defined in one of claims 1 to 35 for the manufacture of an article.

45. Use according to claim 44, wherein the article is an article for electronic products, for telecommunication applications or for data exchange.

46. ​​The use according to claim 44, wherein the article is an article for an autonomous vehicle or for interconnect applications.

47. Use according to any one of claims 44 to 46, wherein the article is produced by injection moulding.

48. Article obtained by injection molding with a composition as defined in one of claims 1 to 35.

Citation Information

Patent Citations

  • Flexible semi-aromatic polyamides with low humidity uptake

    EP1505099A2

  • Semiaromatic polyamide molding compositions and their use

    US20080274355A1

  • Stabilised polyamides containing a copper salt and a phosphine

    US3505285A

  • Composition including a copolyamide and a cross-linked polyolefin

    WO2011015790A2

  • Heat-aging-resistant hydrolysis-resistant polyamide / polypropylene alloy

    CN105199374A